Contemporary musical film - Donnelly, K. J. (Kevin J.); Carroll, Beth (Lecturer in Film and Literature); Hatch, Craig; Donnelly, K. J. (Kevin J.); Dubowsky, Jack Curtis; Carroll, Beth; Fremaux, Stephanie; Bunch, Ryan; Haworth, Catherine; Sapiro, Ian; Baschiera, Stefano, 1977-; Decker, Todd R. (Music and the moving image., 2017)
This edited collection looks closely at the range and scope of contemporary film musicals, from stage adaptations like Mamma Mia! (2008) and Les Miserables (2012), to less conventional works that elide the genre, like Team America: World Police (2004) and Quentin Tarantino's Kill Bill (2003/04).